2021
DOI: 10.3389/fped.2021.659677
|View full text |Cite
|
Sign up to set email alerts
|

Explore the Predictive Value of Peripheral Blood Cell Parameters in Refractory Mycoplasma pneumoniae Pneumonia in Children Over 6 Years Old

Abstract: Background: To determine the predictive value of peripheral blood cell parameters for refractory Mycoplasma pneumoniae pneumonia (RMPP) in children over 6 years old.Methods: A retrospective study was conducted in children with RMPP admitted to the respiratory department of Tianjin Children's Hospital from September 2017 to September 2019, and non-refractory Mycoplasma pneumoniae pneumonia (NRMPP) was selected by the propensity score method and matched according to the ratio of 1:1.5. We analyzed the difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Immunoglobulins are considered potent immunomodulators for various immune-mediated diseases, and it has marked activity against Mycoplasma pneumonia and provide additional protection, especially in patients who do not respond well to antibiotic therapy. Immunoglobulins have been reported to be effective in the treatment of many autoimmune and systemic inflammatory diseases [18][19][20]. Immunoglobulins have significant effects on different immune system effector cells (such as B and T lymphocytes and dendritic cells) and regulate a wide range of genes.…”
mentioning
confidence: 99%
“…Immunoglobulins are considered potent immunomodulators for various immune-mediated diseases, and it has marked activity against Mycoplasma pneumonia and provide additional protection, especially in patients who do not respond well to antibiotic therapy. Immunoglobulins have been reported to be effective in the treatment of many autoimmune and systemic inflammatory diseases [18][19][20]. Immunoglobulins have significant effects on different immune system effector cells (such as B and T lymphocytes and dendritic cells) and regulate a wide range of genes.…”
mentioning
confidence: 99%
“…35 Lee et al 8 confirmed that pleural effusion is a risk factor for nonresponse to treatment or the progression of MPP in children (OR 5.127, 95% CI 1.404-18.727). YY Ling et al 13 found that pleural effusion was an independent risk factor for RMPP in children over six years of age (OR 3.023; 95% CI 1.424-6.420, P=0.004). The current study only deals with the qualitative assessment of pleural effusion and lacks a quantitative evaluation, which may affect its contribution to the early diagnosis of RMPP.…”
Section: Dovepressmentioning
confidence: 99%
“…Among predictive models, including laboratory indicators, recent studies have found that the levels of LDH and CRP 9 in the blood are the best predictors of RMPP. Some studies have also found inflammatory indicators in the blood, such as DD, 10 SF, IL-18, 11 ALB, 12 the neutrophil-to-lymphocyte ratio (NLR) and the mean platelet volume-to-lymphocyte ratio (MPVLR), 13 are suitable for predicting RMPP. Increased IL-17A in bronchoalveolar lavage fluid is an independent risk factor for RMPP.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, known laboratory indicators that can predict the severity of MPP include peripheral blood neutrophil count, Creactive protein (CRP), lactate dehydrogenase (LDH), interleukin-6, interleukin-17A, and D-dimer (9)(10)(11)(12). Models predicting poor prognosis in MPP have also been established and evaluated (6,13).…”
Section: Introductionmentioning
confidence: 99%